Recent Progress in Cerebrovascular Gene Therapy - Sato, Naoyuki; Shimamura, Munehisa; Morishita, Ryuichi (Current Neurovascular Research, 2005)
Gene therapy provides a potential strategy for the treatment of cardiovascular disease such as peripheral arterial disease, myocardial infarction, restenosis after angioplasty, and vascular bypass graft occlusion. Currently, more than 20 clinical studies of gene therapy for cardiovascular disease are in progress. Although cerebrovascular gene therapy has not proceeded to clinical trials, in contrast to cardiovascular gene therapy, there have been several trials in experimental models. Three major potential targets for cerebrovascular gene therapy are vasospasm after subarachnoid hemorrhage (SAH), ischemic cerebrovascular disease, and restenosis after angioplasty, for which current therapy is often inadequate. In experimental SAH models, strategies using genes encoding a vasodilating protein or decoy oligodeoxynucleotides have been reported to be effective against vasospasm after SAH. In experimental ischemic cerebrovascular disease, gene therapy using growth factors, such as Brain-derived neurotrophic factor (BDNF), Fibroblast growth factor-2 (FGF-2), or Hepatocyte growth factor (HGF), has been reported to be effective for neuroprotection and angiogenesis. Nevertheless, cerebrovascular gene therapy for clinical human treatment still has some problems, such as transfection efficiency and the safety of vectors. Development of an effective and safe delivery system for a target gene will make human cerebrovascular gene therapy possible.
Keywords: hemagglutinating virus of Japan